Pengaruh Budaya Kerja Terhadap Akuntabilitas Kinerja Pelayanan Pada Kantor Camat Dungingi Kota Gorontalo - Ical Aditia Mamonto; Gaffar Gaffar; Purwanto Purwanto (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2023)
Problems that appear in the provision of services to the community based on an interview with a community leader said that there had been no notification regarding the requirements for public services being given, letters of approval/permits to marry, arrangements for land deeds that had to be signed by the sub-district head, it was not clear what residents had to fulfill. so that many residents have to go back and forth to the sub-district office, as well as in the case of recording identity cards, there are still many residents who do not know what requirements must be met. Another issue that has not been conveyed openly to the community is the result of monitoring by the sub-district apparatus on the distribution of social assistance carried out by the sub-districts in the Dungingi District area. All the issues raised are closely related to service performance accountability, where sub-district officials are required to convey all matters related to the implementation of public services which are their authority. With these problems occurring, the purpose of this research is to determine the magnitude of the simultaneous and partial influence of work culture on service performance accountability at the Dungingi District Office, Gorontalo City. This research uses a quantitative approach with a survey method. The number of samples in this study were 39 people. The data analysis method uses path analysis. The results showed that work culture in the form of attitudes towards work and behavior at work simultaneously and partially had an effect on accountability for service performance at the Dungingi District Office, Gorontalo City. Thus it can be said that work culture can contribute to the realization of public service performance accountability to citizens..